Pelatihan diversifikasi produk olahan ikan bagi istri nelayan di Gampong Cot Seurani Aceh Utara untuk meningkatkan gemar makan ikan pada anak-anak (Diversification training of fish processed product for fisherman wife in Cot Seurani Village Aceh Utara to improve fish eating pleasure in children) - Erniati, E; Imamshadiqin, I; Erlangga, E; Ezraneti, Riri; Syahrial, S; Imanullah, I (Buletin Pengabdian, 2021)
The aim of this service activity was to socialize and train fishermen's wives inCot Seurani Village, Muara Batu Sub-District, North Aceh District how to process fish. The target of the training was that fishermen's wives understand and are creative in producing fish products as healthy alternative snacks for children during their growth and development stages. This activity had several stages which were program planning, preparation, training to process fish into fish nuggets and dragon feet products. From the program planning stage, the survey showed that: 1) the fishermen's wives did not have sufficient skills to process fish; 2) during the catching season, fish is usually sold at a low price; and 3) the children of the fishermen did not like to eat fish and preferred chicken and other street foods. The result of this service activity was that the participants have already had the skills and practiced directly how to make fish nuggets and dragon feets. In conclusion, the fishermen's wives can now provide fish products for their children.